Using the ADDIE model to design and develop physical education lessons incorporated with a functional training component - Li, Hailing; Cheong, Jadeera Phaik Geok (Frontiers in Public Health, 2023)
Introduction Good physical fitness is the foundation of a healthy lifestyle. For students, the school becomes the main place to improve their physical fitness. The traditional physical education class places little emphasis on improving physical fitness and students’ physical fitness have continued to decline. To address these challenges, this study aimed to design and develop a functional training program that can be incorporated into existing physical education lessons to improve students’ physical fitness levels. Methods This study adopted the instructional design framework of the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model to guide the design and development of the functional training program. After development, the program was implemented and evaluated. Results The results showed the program aroused students’ interest and significantly improved students’ physical fitness. Conclusion This study showed the usefulness of functional training in improving the physical fitness of primary school students. In addition, it provided a reference for how to use functional training in conjunction with the physical education syllabus.